Therapeutic impact of percutaneous spinal biopsy in spinal infection. Issue 948 (5th October 2004) - Rankine, J J; Barron, D A; Robinson, P; Millner, P A; Dickson, R A
Abstract : Objective: To investigate the therapeutic impact of percutaneous spinal biopsy in patients with suspected spinal infection. Design and patients: A review of the case notes and imaging features of 36 patients who underwent percutaneous spinal biopsy was performed. From this group 20 patients with a prebiopsy diagnosis of spinal osteomyelitis were identified. Management before biopsy was noted including the use of antimicrobial therapy. The results of the histology and microbiology were noted along with the subsequent diagnosis and management. Results: Eight of the 20 patients (40%) had received antibiotics before the biopsy. An organism was isolated in 8/20 cases (40%). Of the eight patients on antibiotics, two grew an organism (25%), including one case of candida in a patient receiving flucloxacillin. Out of 12 patients not on antibiotics there were six cases where an organism was isolated (50%). The result of the biopsy led to a change in management in seven of the 20 patients (35%). Conclusions: Many clinicians are treating spinal osteomyelitis empirically with antibiotics before biopsy, but this reduces the chance of isolating an organism and determining antibiotic sensitivity. Despite this biopsy led to a change in management in 35% of cases.